Reconstruction of Norms for Women with Disabilities as Victims of Sexual Violence - Alexsandria Pinkan Larasati; Maudy Dea Aditya; Sabrina Azzahra Cesaria Febrianti; Ratih Fauziah Azzahro; Mawardi Junila Arum; Gilbert Audrict Tanjaya (Universitas Negeri Surabaya, 2025)
This article aims to develop policy recommendations that can be implemented to improve legal protection and accessibility for women with disabilities in the criminal justice system. Women with disabilities are a vulnerable group who often experience physical, social, and structural barriers in accessing justice. The method used in this research is normative juridical. This method relies on the analysis of applicable positive law and is associated with the principles of justice and the protection of human rights. Data was collected through legislation, official documents, and relevant legal literature, including academic studies and reports from disability protection agencies. The results showed that there is a need to revise the law to include special provisions that protect the rights of women with disabilities, as well as increased training for law enforcement officers on issues of disability and gender-based violence. Thus, it is hoped that the criminal justice system in Indonesia will become more responsive, inclusive, and fair in handling cases involving women with disabilities as victims, witnesses, and perpetrators, to achieve substantive justice for all citizens